FAKTOR-FAKTOR PENYEBAB KRISIS AKHLAK DALAM KELUARGA(STUDI KASUS DI DESA GALAK KECAMATAN SLAHUNG KABUPATEN PONOROGO) - Aris Nurhidayah; Rido Kurnianto; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2017)
Abstract: In the research problems that researchers see is the moral crisis of teenagers to the family, the behavior and lack of courtesy towards the family, such as speaking a rough word, very lacking manners, and bad behavior. Teenagers get more influence in the environment outside the home. In the village of Galak, Slahung Sub-district, adolescence was hit by moral crisis. Starting from the behavior, behavior, manners, etiquette, and how to talk to parents. The family plays an important role in education and physical and spiritual body. Environment also affects the morals of teenagers. The formulation of the problem in this research are (1) What are the forms of moral crisis in the family? (2) What are the factors of moral crisis in the family? The purpose of this study are (1) To know the form of moral crisis in the family. (2) To know the factors of moral crisis in the family. To answer these questions researchers used a qualitative approach in his research. In data collection techniques, researchers use methods of interviewing, observation, and documentation. Then, techniques in data analysis are data reduction, data display, and conclusion or verification. The data of this study found that, factors causing the moral crisis in the family in the village Galak Slahung district Ponorogo Regency is (1) environmental factors that is, errors in associating with the environment, adolescent easy to follow the behavior of friends that are less good. (2) family factor that is caused by looseness of religion handling, moral guidance of parent, current of materialistic and secularistic culture. (3) personal factors namely, (1) the talent factor that affects temperament becomes angry, hyper active. (2) factors in the self itself are in the form of deficiencies in the formation of the conscience, the inability to adapt to the environment, the inability of emotional control, failure in school and association.